Confiscation of Crypto Asset Evidence: Legal Challenges in Cybercrime Enforcement in Indonesia - I Gede Widhartama; Wulanmas Frederik; Merry Elizabeth Kalalo; Herlianty Y.A. Bawole (International Journal of Law, Environment, and Natural Resources, 2025)
The development of information technology has introduced crypto assets as an innovation in the global financial system. The emergence of crypto assets presents both opportunities and challenges, particularly in the enforcement of cybercrime law in Indonesia. Their decentralized, anonymous, and cross-border nature makes them difficult to trace and highly vulnerable to misuse for crimes such as money laundering, online fraud, and terrorism financing. Within the national legal framework, regulatory ambivalence persists: Bank Indonesia prohibits the use of crypto as a means of payment, while Bappebti legitimizes it as a futures commodity. This dualism creates complex legal challenges, especially when crypto assets are treated as evidence in criminal proceedings. The Criminal Procedure Code (KUHAP), which remains oriented toward conventional evidence, has not accommodated the unique characteristics of digital assets, resulting in the seizure and confiscation of crypto assets through broad interpretations that often invite conflicting views and pretrial disputes. This research adopts a normative-empirical juridical approach using a statute approach, supported by secondary data and interviews. The findings reveal that the regulation of crypto asset confiscation in Indonesia remains fragmented, spread across multiple legal instruments, and lacks explicit technical guidance. Consequently, weaknesses persist in legal certainty, procedural effectiveness, third-party protection, and Indonesia’s alignment with international standards. Therefore, this article recommends establishing comprehensive digital asset confiscation regulations, enhancing law enforcement technical capacity, clarifying institutional authority, and integrating national mechanisms with international standards such as the FATF and the Budapest Convention to ensure effective and legally certain implementation consistent with the rule of law.